Taboo censorship: strategy for translating taboo expressions in Indonesian–Arabic subtitles of Pengepungan di Bukit Duri - Muhamad Saiful Mukminin; Muhammad Habibie Alfath; Aninda Ayu Sitorismi; Farrah Chaiya Mas; Eman Ibrahim Mohammed Abubaker (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Taboo expressions in language are often considered inappropriate because they may violate norms of politeness and certain cultural values. In the context of audiovisual translation, particularly film subtitling, taboo expressions are frequently not translated explicitly. This practice is known as the taboo censorship strategy. This study aims to examine the forms of taboo expressions, the application of taboo censorship strategies, and the factors underlying their use in the film Pengepungan di Bukit Duri. The study adopts a qualitative approach using descriptive, comparative, and interpretative methods. The data consist of taboo expressions found in the dialogue of the film Pengepungan di Bukit Duri along with their translations in Arabic subtitles. Data were collected through viewing and note-taking techniques and were analyzed using an interactive data analysis model consisting of data reduction, data display, and conclusion drawing. The findings show that the subtitle translator of Pengepungan di Bukit Duri employed taboo censorship strategies in translating various types of taboo expressions, including those related to animals, mental disorders, and sexual organs and acts. The application of this strategy is influenced by differences in politeness norms between the source and target cultures, the need to soften expressions through euphemism, and the technical constraints of subtitling, which require messages to be conveyed concisely and clearly. Thus, the translator functions as a cultural mediator who seeks to balance fidelity to the source text with social and cultural acceptability for the target audience.